2018
DOI: 10.1186/s40510-018-0218-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision in adult patients with class III malocclusion: surgery versus orthodontics

Abstract: BackgroundOne of the most controversial issues in treatment planning of class III malocclusion patients is the choice between orthodontic camouflage and orthognathic surgery. Our aim was to delineate diagnostic measures in borderline class III cases for choosing proper treatment.MethodsThe pretreatment lateral cephalograms of 65 patients exhibiting moderate skeletal class III were analyzed. The camouflage group comprised of 36 patients with the mean age of 23.5 (SD 4.8), and the surgery group comprised of 29 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 19 publications
0
88
0
13
Order By: Relevance
“…Lately, Islami et al [22], concluded that Holdaway angle and Wits appraisal were able to differentiate between the patients suitable for orthodontic camouflage or surgical treatment. Cases with a Holdaway angle greater than 10.3˚ and Wits appraisal greater than −5.8 mm would be treated successfully by camouflage, while those with a Holdaway angle of less than 10.3˚ and with Wits appraisal less than −5.8 mm can be treated surgically For this patient, the etiology of his Class III malocclusion was expressed through maxillary retrusion and mandibular protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Islami et al [22], concluded that Holdaway angle and Wits appraisal were able to differentiate between the patients suitable for orthodontic camouflage or surgical treatment. Cases with a Holdaway angle greater than 10.3˚ and Wits appraisal greater than −5.8 mm would be treated successfully by camouflage, while those with a Holdaway angle of less than 10.3˚ and with Wits appraisal less than −5.8 mm can be treated surgically For this patient, the etiology of his Class III malocclusion was expressed through maxillary retrusion and mandibular protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which this happens is highly variable and to a large extent unpredictable. Some articles have mentioned criteria by which a decision can be made regarding camouflage versus surgical treatment of Class III cases [19,20,21]. The case selection criteria for distalisation are varied in the literature probably due to the different treatment modalities usedskeletal anchorage, proclination of the upper anterior teeth, retroclination of the lower anterior teeth by class III elastics, or lower premolar extractions [17,18].…”
Section: Case Selection For Class III Camouflage Casesmentioning
confidence: 99%
“…Class III malocclusion is a complex condition in terms of diagnosis and treatment planning [1,2]. In the recent years, the demand of class III patients for surgical correction of their malocclusion has greatly increased [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%